Evaluating the Quality of Health Professions Learning Environments: Development and Validation of the Health Education Learning Environment Survey (HELES). Issue 3 (September 2020) - Rusticus, Shayna A.; Wilson, Derek; Casiro, Oscar; Lovato, Chris
The learning environment can be broadly conceptualized as the physical, social, and psychological context in which learning and socialization takes place. While there is now an expectation that health professions education programs should monitor the quality of their learning environment, existing measures have been criticized for lacking a theoretical foundation and sufficient validity evidence. Guided by Moos's learning environment framework, this study developed and preliminarily validated a global measure of the learning environment. Three pilot tests, conducted on 1, 040 undergraduate medical students, refined the measure into the 35-item Health Education Learning Environment Survey (HELES), which consists of six subscales: peer relationships, faculty relationships, work–life balance, clinical skills development, expectations, and educational setting and resources. A final validation study conducted on another sample of 347 medical students confirmed its factor structure and examined its reliability and relation of the HELES to the Medical School Learning Environment Survey (MSLES). Subscale reliabilities ranged from .78 to .89. The HELES correlated with the MSLES at .79. These results indicate that the HELES can provide a valid and reliable assessment of the learning environment of medical students and, as such, can be used to inform accreditation and program planning in health professions programs.